European Union law : text and materials - Chalmers, Damian (Cambridge University Press, 2014)
As the preferred choice of both teachers and students, this textbook offers an unrivalled combination of expertise, accessibility and comprehensive coverage. The new edition reflects the way the economic crisis has impacted the shape and nature of European Union law. Materials from case law, legislation and academic literature are integrated throughout to expose the student to the broadest range of views. Additional online material on the application of EU law in non member states and on rulings on the Fiscal Compact ensures the material is completely current. The new edition includes a timeline which charts the evolution of the EU project. Written in a way which encourages sophisticated analysis, the book ensures the student's full engagement with sometimes complex material. More importantly, it offers the clarity which is essential to understanding. A required text for all interested in European Union law.